Effect of Raw Materials and Thickening Agents on The Physicochemical and Sensory Properties of Snapper-Based Kekian - Sutandi, Agus; Kusumawati, Eni; Maulidilla Fitri, Fadillya; Haryanto, Haryanto (Media Gizi Indonesia, 2026)
Stunting in toddlers is associated with an unbalanced diet and insuffcient intake of animal protein, particularly fish. One of the main factors contributing to the low consumption of fish is the complexity of fish processing, especially the handling of fish heads, skin, and trimmings. The objective of this study was to evaluate the efffects of different raw materials and thickening agents on the physicochemical properties and sensory characteristics of snapper-based kekian. The research employed an experimental approach using a Randomized Complete Group Design (RCGD) with 16 treatment combinations and two replications. The first factor was the type of raw material: D1 (chicken meat, control), D2 (snapper  head), D3 (snapper trimmings), and D4 (snapper fillet). The second factor was the type of thickening agents: P1 (without thickening agen, control), P2 (transglutaminase enzyme), P3 (carrageenan), and P4 (a combination of transglutaminase enzyme and carrageenan). Kekian was prepared according to the specified formulations and treatments. Physicochemical and sensory data were analyzed using analysis of variance (ANOVA). The results showed that differences in raw materials significantly affected sensory characteristics, protein content, fat content, moisture content, hardness, springiness, and resilience of snapper-based kekian (p<0.05). Variations in the proportion and quality of fish meat influenced the physicochemical properties of the product. In contrast, the use of different thickening agents did not significantly affect the physicochemical properties of the snapper-based kekian (p>0.05). However, the use of transglutaminase enzymes tended to reduce the elasticity of the product.